THE ESSENCE OF THE FORMATION OF THE MOTIVATIONAL MECHANISM OF ENTERPRISE IN THE CONDITIONS OF THE ECONOMY TRANSFORMATION - Hetmanenko, O. V. (Science and Transport Progress, 2008)
An essence of forming the motivational mechanism of enterprise is considered; a difference between concepts of «motivation» and «stimulus» is presented.